Synopsis: Enhancing rural income diversification in Rwanda: Opportunities and challenges - Schmidt, Emily; Mugabo, Serge; Rosenbach, Gracie (International Food Policy Research Institute, 2024)
This study describes the employment patterns of rural households in Rwanda and explores their challenges and opportunities for rural income diversification. Detailed analysis using a 2022 rural household smallholder survey on agricultural production and employment in Rwanda, reveals that: • Agricultural wage labor is the dominant source of off-farm income and is the primary means of supplementing rural household income. This is different than other LMICs where households are more likely to develop nonfarm enterprises that bring in extra income and diversify the rural economy towards more value-added output while also increasing demand for rural inputs. • This research suggests that factors like access to education and financial services are key factors to employment decisions and improved rural urban linkages.